Factors affecting safety culture in chemical industries of Pakistan - Safdar, Umar; Ferguson, David; Badir, Yousre; Juthathip Jongwanich; AIT Fellowship; Higher Education Commission (HEC), Pakistan (Pathum Thani, Thailand : Asian Institute of Technology, 2013)
Occupational health and safety encompasses the social, mental and physical well - being of the workers. Work plays a cen tral role in people{u2019}s lives . Poor working conditions have the potential to affect a workers health and safety. It is moral and often legal responsibility of employers to maintain a safe and healthy environment at work areas. Work related accidents and dise ases are common in all parts of the world and often have many direct and indirect negative consequences for workers and their families. A single accident or illness can mean enormous financial loss to both worker and employee therefore researchers have pro ved that there is strong relationship between safety and performance. Safety culture is sub culture of overall corporate culture and according to Williams et al (1989) t he perception of employees about organizational goals, objectives and vision may differ from functional areas to functional areas, hierarchical level to hierarchical level even from individual to individual . Successful occupational health and safety practices require the collaboration and participation of both employees and workers. However the priorities of different dimension in mind of workers may differ than employer{u2019}s perception. The Literature shows that most of the work done in this field is based upon developed countries and very less has been done in developing countries especially i n Pakistan. This study examined and explored the prioritized determinants of safety culture in chemical industry of Pakistan. In this study 50 workers and managers from three different chemical industries were asked to prioritize the different dimensions of safety culture through questionnaires . It was found that management commitment, personal priorities and work environment are top prioritized dimension of safety culture. It was found that there is no significant difference between the perception of wor kers and work supervisors, but there is significant difference between workers and managers perceptions regarding involvement of workers in policies and procedure design. Study also found the significant difference between workers and manager{u2019}s perception related to training of employees; managers give high priority to on job training, while workers give high priority to training at specialized school. Study didn{u2019}t find any difference in male and female employees
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research report (M.B.A.) - Asian Institute of Technology, 2013
Keywords: Chemical industry -- Safety measures -- Pakistan